Agricultural input and output: Marketing reforms in African countries: Final project summary - Badiane, Ousmane (International Food Policy Research Institute, 1997)
Objective of research: i) to raise the understanding of the conditions for the successful reform of agricultural input and output markets in African countries and ii) to identify strategies to complete the transition to competitive and efficient output distribution and input delivery systems. Through the survey of the experiences of selected countries, it was expected to help understand the types, extent, and seriousness of obstacles to market reform implementation. Given its short term character, the project did not look in-depth into the implications of reforms at the farm household level, but laid the ground work for a further investigation of those issues by IFPRI's wider input and output market reforms.